STUDY OF VIBRATION SUPPRESSION SYSTEM OF HIGH ALTITUDE PLATFORM BASED ON MR DAMPER - CHEN GuiLiang; CAO WeiTao; YANG Dong; ZHANG ShouLin; LI HeLi; ZHANG GaiPing (Jixie qiangdu)
Based on the high attitude platform of building slabstone-installing robot with independent development,research was carried out about multi-DIM vibration. The paper firstly constructs the system with two degrees of freedom parallel mechanism as the main body and rotating MR damper as actuator. The dynamics equation of the vibration system is established by using Lagrange equation. The paper analyzes the vibration characteristics and designs a kind of rotary MR damper based on a shear mode of magneto rheological fluid. The mechanical characteristics of MR damper is analyzed. The kinematics and kinetic analysis of parallel mechanism is done. The multi-DIM vibration suppression works quickly based on the position of platform according to the kinematics equation. Finally the simulation experiment of this system of multi-DIM vibration suppression is introduced with the aid of to calculate and analysis whether the model is effective and feasible.